2020
DOI: 10.3390/ijerph17020460
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sense of Community Responsibility on Residents’ Altruistic Behavior: Evidence from the Dictator Game

Abstract: Understanding the new mechanism of altruistic behavior is pivotal to people’s health and social development. Despite the rich literature on altruism, this is the first study exploring the association between the sense of community responsibility (SOC-R) and altruistic behavior by repeated dictator games. Data were gathered from 95 residents (30% male; M age = 33.20 years). Demographic variables, money motivation, and SOC-R were measured. The results revealed that there was a significant positive correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…There is a great body of literature finding evidence for a relationship between perceived responsibility and prosocial behavior. Whereas different approaches emphasize different aspects of responsibility, results are consistent in that prosocial behavior increases when people perceive a high degree of moral obligation, duty, or personal responsibility to help others (e.g., Amato et al., 1984 ; Brañas-Garza, 2007 ; Bruttel and Stolley, 2018 ; D'Antonio, 2014 ; Erlandsson et al., 2015 ; Schwartz and Clausen, 1970 ; Yang et al., 2020 ). In the present study, we mainly focus on the individuals’ perception of his/her own responsibility to show prosocial behavior.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…There is a great body of literature finding evidence for a relationship between perceived responsibility and prosocial behavior. Whereas different approaches emphasize different aspects of responsibility, results are consistent in that prosocial behavior increases when people perceive a high degree of moral obligation, duty, or personal responsibility to help others (e.g., Amato et al., 1984 ; Brañas-Garza, 2007 ; Bruttel and Stolley, 2018 ; D'Antonio, 2014 ; Erlandsson et al., 2015 ; Schwartz and Clausen, 1970 ; Yang et al., 2020 ). In the present study, we mainly focus on the individuals’ perception of his/her own responsibility to show prosocial behavior.…”
Section: Introductionmentioning
confidence: 69%
“…Specifically, we showed that levels of prosocial behavior were associated with the giver's responsibility and the recipients' vulnerability to COVID-19, which is in line with previous research. Previous research (e.g., D'Antonio et al, 2014;Amato et al, 1984;Fisher & Ma, 2014;Kappes et al 2018;Yang et al, 2020) using comparable methods found large effects (d = 0.94 to d = 1.25) of giver's responsibility to help on prosocial behavior and moderate effects (d = 0.31 and d = 0.57) of the recipients' vulnerability on prosocial behavior. Our effects (d = 1.01 and d = 0.43) fall in these ranges of effect sizes, speaking for the generalizability of these effects to the pandemic (in direction and size).…”
Section: Discussionmentioning
confidence: 90%
“…From a psychosocial perspective, prosocial behaviours have been explained using constructs revolving around helpers' sense of responsibility for others (Yang et al, 2020 ). At a community level, responsibility towards others has been understood as sense of community responsibility (SoC‐R), which refers to the feeling of responsibility towards other community members and the community as a whole, that enhances individuals' motivation to help (Nowell & Boyd, 2010 ; Nowell & Boyd, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…If they reject it, neither of them receives any of the money. A study by Yang et al ( 2020 ) found a positive correlation between a sense of community responsibility (SOC-R) and altruism behaviour (AB). Their regressions demonstrated a linear relationship, with SOC-R as the predictor and AB as outcome.…”
Section: Methodsmentioning
confidence: 99%